Indian Recordings (Schomerus 1929); Booklet - Remmer, Ulla (Verlag der Österreichischen Akademie der Wissenschaften, 2019)
The CD publication features 30 sound recordings, chiefly recitations of classical Tamil poetry, made by Hilko Wiardo Schomerus in Madras (Chennai) in 1929. What is new and special about this release is the publication of the sources, of which hitherto no (or only little) notice has been taken.Booklett: https://e-book.fwf.ac.at/o:1308 1. Introductory notes, comments and transcriptions: https://e-book.fwf.ac.at/o:13172. Documents: https://e-book.fwf.ac.at/o:13213. Protocol and Sound recordings: https://e-book.fwf.ac.at/o:1353